Studying law at university : everything you need to know - Chesterman, Simon; Rhoden, Clare (St Leonards, N.S.W. : Allen and Unwin, 1999)
This book is divided into three parts. In Part I, "Surviving law", by looking at why people decide to study law, the types of jobs it leads to, different ways of structuring degrees and the sorts of courses law offers readers. In Part II, "Understanding law", demystifying law by introducing you to some of its crucial concepts. And in Part III, "Using law", looking at how to apply the skills developed in Part II.
Keywords: Australia; Law; Law -- Study and teaching -- Australia; Law students -- Australia -- Handbooks, manuals, etc